Comparing bioenergetic models for the optimisation of pacing strategy in road cycling - Sundström, D.; Carlsson, P.; Tinnsten, M. (Sports Engineering, 2014)
Road cycling performance is dependent on race tactics and pacing strategy. To optimise the pacing strategy for any race performed with no drafting, a numerical model was introduced, one that solves equations of motion while minimising the finishing time by varying the power output along the course. The power output was constrained by two different hydraulic models: the simpler critical power model for intermittent exercise (CPIE) and the more sophisticated Margaria-Morton model (M-M). These were compared with a constant power strategy (CPS). The simulation of the three different models was carried out on a fictional 75 kg cyclist, riding a 2,000 m course. This resulted in finishing times of 162.4, 155.8 and 159.3 s and speed variances of 0.58, 0.26 and 0.29 % for the CPS, CPIE and M-M simulations, respectively. Furthermore, the average power output was 469.7, 469.7 and 469.1 W for the CPS, CPIE and M-M simulations, respectively. The M-M model takes more physiological phenomena into consideration compared to the CPIE model and, therefore, contributes to an optimised pacing strategy that is more realistic. Therefore, the M-M model might be more suitable for future studies on optimal pacing strategy, despite the relatively slower finishing time.